Ograničavajući čimbenici izostanka aktivnosti na šumoposjedima u Republici Hrvatskoj - MIMIC model : Constraining factors of activities in Croatian forest estates - MIMIC model - Žunić, Marijana (Array, 2019)
The purpose of this paper was to determine the share of active and inactive forest owners in Croatia and to identify potential causes for underuse of wood resources and their most important predictors based on inactive forest owners sample. We interviewed 1007 randomly selected forest owners on Croatian territory with a telephone survey. Of the total sample, 60% of forest owners believe that they efficiently manage their forests while 40% are inactive (Table 1). In order to determine the most important reasons and causes for inactive forest owners not cutting more, additional questions were asked. They were provided by 19 statements describing possible reasons for underuse of wood resources. Then, on Likert’s scale from 1 (not important at all) to 5 (very important) they expressed their level of agreement with a particular statement (Table 2). The statements were condensed into three dimensions by explanatory factor analysis with eigenvalue approach. Factors were interpreted as: (1) factor of qualifications and knowledge constraints, (2) factor of passiveness and forest conservation and (3) factor of physical constraints (Table 2). Statistically acceptable model was established by confirmatory factor analysis approach (Figure 2). The pronounced processes of structural changes in forest ownership composition, as well as in socio-demographic and forest property characteristics, are evident across Europe consequently influencing the intensity of private forest management. Within the aforementioned, we used gender, age, education, working status, the distance between the forest and the place of residence, the size of the settlement and the knowledge of forest property boundary lines as independent variables for management constraining factors model construction (Figure 1).